Intradermal hepatitis B vaccination in thalassaemia. Issue 5 (May 1990) - Leonardi, S; Leggio, T; Sciacca, A; Di Gregorio, F; Musumeci, S
Abstract : Fifty six children with thalassaemia, and 118 healthy subjects, who had all been immunised with an intramuscular injection of hepatitis B vaccine (HB-VAX) into the deltoid area three years previously, were given booster doses intradermally. All responders (good = hepatitis B surface (HBs) antibody titre greater than or equal to 10 U/l; poor = HBs antibody titre less than 10 U/l) showed pronounced increase in anti-HBs titre, in many cases above 1000 U/l. We also found positive HBs antibody response after further doses (two to four) at intervals of 15 days in non-responders (those patients who formerly had shown no HBs antibody titre after the conventional schedule of vaccination). The humoral response was always preceded by a delayed tissue hypersensitivity reaction. In conclusion, vaccine against hepatitis B virus given in low doses intradermally produces an effective immune response; it is a useful method of enhancing the antibody response in exposed patients, and of vaccinating those who do not respond initially.